Biodrying of Dewatered Secondary Sludge: Behavior of Dynamic Respiration Index (Dri) and Energy Release Under Different Operating Conditions - Castillo-Nara, A; Leiva-Lobos, E; Huilinir-Curio, C; Montalvo-Martinez, S; Cottet-Bustamante, L (John Wiley and Sons Ltd, 2020)
BACKGROUND: Biological activity monitored through the dynamic respiration index (DRI) and the calculation of biological heat generation (Qbio) through O2 consumption has been reported only scarcely in the case of biodrying. Therefore, the present work studies the DRI and Qbio for a dewatered secondary sewage sludge biodrying process under different operating conditions: airflow rate (AFR) and initial moisture content (IMC). RESULTS: It was found that AFR has an important effect on oxygen consumption, with higher DRI (≤6 gO2 kgVS–1 h–1) at higher AFR for different studied IMCs. IMC also affects the DRI, with higher values of DRI at higher IMC. Determination of the Qbio indicated that its calculation through O2 consumption provided better explanations of the water removal of the process. AFR also affects water removal and volatile solids (VS) degradation, with greater water removal (c. 30%) and lower VS degradation (c. 3.6%) at lower AFR. CONCLUSIONS: AFR strongly affects the DRI, with higher DRI at low AFR. The calculation of Qbio through O2 consumption is recommended. © 2019 Society of Chemical Industry. © 2019 Society of Chemical Industry